Grievance Arbitration. A Model for the Study of Policy Change - Gandz, Jeffrey (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
A model is developed which explains the factors involve d in a trade union's decision to pres s a grievance to arbitration. This model is then used to analyze the impact of policy initiatives designed to reduce the costs of arbitration, speed up the process and facilitate mediation prior to arbitration. Finally a number of research strategies for validating the model are proposed and discussed.